Absorption coefficients of aerosols obtained from in situ data in Covilhã, central Portugal - Mogo, Sandra (2018)
Since October 2009 an aerosol measurement data set was started at Covilhã, a small town located in the region of Beira Interior (Portugal) ain the interior a of the Iberian Peninsula. a Until July 2010, the ambient light-absorption coefficient, σ (470 nm), σ (522 nm) and σ (660 nm), presented a daily mean value of 14.2Mm-1 (StD=8.6Mm-1), 12.1Mm-1 (StD=7.3Mm-1) and 9.6Mm-1 (StD=5.7Mm-1), respectively. Monthly variations and daily cycle are presented in this work.